IMPLIKASI POLITIK DAN EKONOMI TERHADAP KERJA SAMA PERDAGANGAN ANTARNEGARA ASEAN MENGGUNAKAN MATA UANG RESMI ASEAN - Remeiliza Fitri (Universitas Khairun, 2024)
This research investigates the impact of economic trade cooperation among ASEAN countries with the introduction of the official ASEAN currency. This regional currency is considered crucial in facilitating economic integration in ASEAN, even though it faces significant challenges, especially in terms of varying economic stability among member countries. By combining political and economic analysis, this study aims to provide a better understanding of the implications of the implementation of the ASEAN single currency on trade dynamics and overall regional stability.